DETERMINASI FINANCIAL DISTRESS PADA PERUSAHAAN FARMASI DI INDONESIA - Trixi Farhan Yaziq; Nining Ika Wahyuni; Oktaviani Ari Wardhaningrum (UNIVERSITAS DHARMAWANGSA, 2026)
The volatility experienced by pharmaceutical companies during and after the COVID-19 pandemic has intensified operational and financial pressures, raising concerns regarding financial sustainability and the potential for financial distress. This study aims to analyze the effect of profitability, leverage, and liquidity on financial distress in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Employing a quantitative approach with an associative causal design, the research uses purposive sampling to obtain 11 companies with 55 firm-year observations. Financial distress is measured using the Altman Z-Score Model, while profitability, leverage, and liquidity are represented by Return on Equity (ROE), Long-Term Debt to Equity Ratio (LDER), and Cash Ratio (CAR). Panel data regression with the Fixed Effect Model (FEM) and robust standard errors is applied to analyze the relationships among variables. The results reveal that profitability and leverage do not significantly affect financial distress, whereas liquidity has a significant negative effect, indicating that firms with stronger short-term liquidity are less exposed to financial instability. These findings imply that maintaining adequate liquidity is a key strategy for enhancing financial resilience in the pharmaceutical industry, especially in periods of heightened uncertainty.